(untitled) (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
The freedom in the use of social media becomes a common means in voicing opinions and expressions by issuing words or phrases of blasphemy (Hate Speech) in social media like Facebook. Hate speech and blasphemous words are easily spread across social and general media not found that have transgressed the limits and can trace the unrest. To find out what the users of social media especially Facebook we have issued words or phrases of blasphemy on the basis of this report occurred. The study was conducted by using TF-IDF weighting algorithm and VSM (Vector Space Model) calculation, while the data used was the 30 users post using Graph API. This research resulted in search with recall value: 2/2 = 1 which means the result of the relevant document and the precision value of the search result is 2/13 = 0,154 which means result also raises irrelevant search result. Percentage of hate speech equivalence value was 43%.